The Image of New Europeans in Swedish Newspapers. Power and Solidarity in the Swedish Press Debates about ES Enlargement - Jonkutė, Raimonda (Respectus Philologicus, 2005)
In times of big social changes, members of a society are anxious about their insecure future and often tend to use the so-called „scapegoat” strategy (e. g.,Resigl&Wodak) and treat disabled people, immigrants and other minority groups negatively. Critical discourse analysis investigates these manifestations in the texts with the help of functional grammar and its ideational aspect (Halliday), where the analysis of the interaction of verb processes and participants allows the interpretationof the results by means of concepts „power” and „solidarity” (e. g. Hodge & Kress). This article focuses on the image of the new EU members as „social tourists” rushing to the country and abusing the social insurance systems in the Swedish press debate while anticipating the EU enlargement in May 2004.
Keywords: EU enlargement; press debate; „socials tourism / social tourists; critical discourse analysis; functional grammar; power; solidarity